Are there Regional Differences in Tc-Uptake? - Wieler, H.; Ebert, A. (Nuklearmedizin - NuclearMedicine, 1989)
The 99mTcO4-uptake (TcTU) was measured in 363 clinically and by laboratory findings euthyroid patients without history of hyper- or hypothyroidism, no evidence of iodine contamination and with a Delta-TSH <2,5 IU under a longterm suppressive thyroxine therapy. The medians of TcTU in the different regional groups from the Federal Republic of Germany (mail zip code 2000-8000) were not statistically different from each other, indicating that under suppression with thyroxine the effect of the iodine supply on TcTU is nearly negligible, and that, using the same method, results from different nuclear medicine departments should not differ significantly from each other.